Jimma, the first Medical School founded by Cuba in the African horn - Miguel Alfonso Álvarez Fornaris; Estela Morales Peralta; Fidel Cathcart Roca (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction:  Internationalism has been a distinctive feature of the Cuban Revolution, highlighting the international aid in health care and the formation of human resources, issue that we consider should be better known. Objective: To describe some experiences in the foundation of the first Medical School created with Cuban medical personnel in the African horn, in the town of Jimma, Ethiopia in 1985. Material and Methods: A historical-descriptive study was conducted.  It was based on bibliographic reviews, interviews, and an exchange of correspondence between the participants and their relatives. Development: Ethiopia, one of the most underdeveloped and poor countries in Africa, had two Medical Schools and around 400 doctors for a population of about 40 million inhabitants. Cuba collaborated with the facilitation of a teaching staff for the foundation of a third school and the improvement of the training of health care personnel.  The education was based on the ethical foundations of our Medicine. As a distinctive feature, the curriculum had to be adapted to the one which was used in that country.  The classes were taught in English and the students were subjected to an external examination at the end of each course. The first group of teachers stayed there for more than 31 months, and taught more than 200 students, in two consecutive courses. The first 67 doctors graduated In 1990. Conclusions:The Medical School founded by Cuba in Jimma, Ethiopia, constitutes an important milestone in our history of Cuban internationalist aid in health care and education. Keywords: History, Internationalism, Medical Teaching, Medical School, Jimma, Ethiopia, African Horn.